Peningkatan Organizational Citizenship Behavior (OCB) melalui Penguatan Efikasi Diri dan Kepuasan Kerja - Neneng Novita Nidea Sari; Muhamad Entang; Griet Helena Laihad; Hendarman Hendarman (Universitas Pakuan, 2022)
Improving Organizational Citizenship Behavior (Ocb) through Strengthening Self-Efficiency and Job SatisfactionThe research aims to find the efforts in order to improve organizational citizenship behavior (OCB) through a study on the strength of the correlation between research variables, namely; 1) the strength of the correlation between self-efficacy and organizational citizenship behavior, 2) the strength of the correlation between job satisfaction with organizational citizenship behavior, 3) the strength of the correlation between self-efficacy and job satisfaction simultaneously with organizational citizenship behavior. This research was conducted at the Private Junior High School at Central Bogor District, Bogor City in 2021. The amount of sample 134 taken by proportional random sampling. Hypothesis testing conducted at the 0.05 significance level. The research produced three conclusions, such as; 1) there was a positive and highly significant correlation between self-efficacy with organizational citizenship where the correlation coefficient was ryl = 0.774 and self- efficacy contributes 59.9% to organizational citizenship behavior, 2) there was a positive and highly significant correlation between job satisfaction with organizational citizenship behavior where the correlation coefficient was ry2 = 0.751 and job satisfaction contributed 56.3% to organizational citizenship behavior, 3) there was a positive and highly significant correlation between self-efficacy and job satisfaction simultaneously with organizational citizenship behavior where the correlation coefficient was ry12 = 0.806 and self-efficacy and job satisfaction simultaneously contributed 65% to organizational citizenship behavior. Based on the conclusions, the organizational citizenship behavior can be increased through self-efficacy and job satisfaction.